Evaluation of different erosion models for predicting guide vane wear in Francis turbine - Shrestha, Rakish; Shrestha, Kushal; Chitrakar, Sailesh; Thapa, Bhola; Neopane, Hari Prasad; Qian, Zhongdong; Guo, Zhiwei (Frontiers in Mechanical Engineering, 2025)
Guide vanes (GVs) are one of the components of the Francis turbine that are most vulnerable to erosion. Presence of hard minerals including feldspar and quartz cause erosion on the surface of GVs. This results in damage and disturbances in the functioning of the turbine. Computational Fluid Dynamics (CFD) methods are useful to estimate erosion but are dependent significantly on erosion models used for simulations. A three guide vane cascade (3GV) rig is a simplified setup that recreates the flow around GVs. Previous studies have used the setup to visualize the secondary flows around the GVs using Particle Image Velocimetry (PIV) and CFD techniques that could be one of the major causes of erosion in Francis turbine. In this study, an Eulerian-Lagrangian approach with Reynolds Averaged Navier Stokes (RANS) based Shear Stress Transport (SST) turbulence model has been used to develop a numerical model of the same rig. The erosion caused by the sediment-laden flow has been quantified and visualized by employing Finnie, Nandakumar, Oka, and Tabakoff and Grant erosion models. This study has been conducted to determine which of the erosion model predicts the erosion pattern closer to the real case of eroded GV of Jhimruk Hydro-Electric Plant (HEP). The focus of the study is the clearance gap (CG) of the GV. By dividing the CG into sections and comparing the erosion predictions by different erosion models with the actual erosion, Finnie erosion model is found to be the most suitable model for this application. The severity and area affected due to erosion as predicted by this model is found to most closely match the erosion observed in the CG of the real hydropower plant’s GV, specially at three different locations: trailing edge of suction side (SS-TE), leading edge of suction side (SS-LE) and the middle of the leading edge (MS-LE).